2019
DOI: 10.18051/univmed.2019.v38.10-16
|View full text |Cite
|
Sign up to set email alerts
|

Acupressure has not an analgesic effect in patients with renal colic: a randomized controlled trial

Abstract: Background<br />Easing renal colic (RC) pain is of the most important issues in the emergency departments. This study was conducted to investigate the analgesic effects of intravenous paracetamol in comparison to acupressure and intramuscular diclofenac in patients with RC.<br /><br />Methods<br />This randomized clinical trial was conducted on 96 eligible patients with RC, visiting the Emergency Department of Imam Reza Hospital of Mashhad, Iran. The participants were selected by consec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Corresponding to these findings, Düzel et al (2023) reported beneficial effects in reducing pain in patients after angiography [ 34 ]. However, one study did not find a significant effect of acupressure on the pain of colic patients [ 11 ]. The lack of previous studies on the impact of acupressure on pain during ESWL limits the opportunity for further comparison and discussion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Corresponding to these findings, Düzel et al (2023) reported beneficial effects in reducing pain in patients after angiography [ 34 ]. However, one study did not find a significant effect of acupressure on the pain of colic patients [ 11 ]. The lack of previous studies on the impact of acupressure on pain during ESWL limits the opportunity for further comparison and discussion.…”
Section: Discussionmentioning
confidence: 99%
“…Undesirable effects of NSAIDs include allergy, gastrointestinal bleeding, decreased renal blood flow, and even kidney failure [ 10 ]. Additionally, the use of opioids may cause various side effects such as nausea, vomiting, low blood pressure, and respiratory depression [ 11 ]. Therefore, it is essential to develop non-pharmacological methods to control vital signs and reduce patient pain [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation